2021
DOI: 10.1177/1069031x20983806
|View full text |Cite
|
Sign up to set email alerts
|

Not All Wrongdoers Are Equal in the Public Eye: A Moderated Mediation Model of Country Stereotypes, Condemning Emotions, and Retaliatory Intent in Corporate Crises

Abstract: Corporate crises generate condemning emotions and retaliatory intent toward wrongdoing companies. However, not all wrongdoers are equal in the public eye. Consumers’ prior beliefs about a company’s country-of-origin may bias these responses. In three experimental studies (combined N = 1,008), the authors (1) establish that country stereotypes of warmth – but not of competence – can buffer condemning emotions and retaliatory intent toward a wrongdoing company. They further (2) reveal the psychological mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 94 publications
4
20
0
Order By: Relevance
“…These findings complement those of previous studies (e.g. Barbarossa and Mandler, 2021; Barbarossa et al. , 2022; Khamitov et al.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings complement those of previous studies (e.g. Barbarossa and Mandler, 2021; Barbarossa et al. , 2022; Khamitov et al.…”
Section: Introductionsupporting
confidence: 92%
“…Finally, it confirms the amplifying role of consumer animosity in brand nationality, UBA, and the desire for revenge/reconciliation in the brand scandal context. The findings advance our knowledge of how brand nationality and consumer animosity jointly affect UBA and subsequent revenge and reconciliation reactions (Barbarossa and Mandler, 2021; Barbarossa et al. , 2022; Fong et al.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Shea and Hawn (2019) found that national stereotypes play a role in the case of corporate social (ir)responsibility; companies from high-warmth (by default competent) countries receive lower corporate social responsibility (CSR) rewards and pay higher corporate social irresponsibility (CSI) penalties, but this effect is moderated by competence. However, another study reveals that warmth perception of a country can buffer condemning emotions and retaliatory intent toward an offending company from this country when it involves an ability (vs value) crisis, and this effect is underlined by decreased greed attribution (Barbarossa and Mandler, 2021). Overall, it appears that country warmth constitutes a security base preventing companies from being seriously hurt under conditions of irresponsibility or crisis.…”
Section: The Application Of the Scm In Marketingmentioning
confidence: 99%